THE ROLE OF DIETARY PATTERNS AND NUTRIENTS IN SCHIZOPHRENIA: A LITERATURE REVIEW - Natalia Kraciuk; Alicja Bury; Karol Bartecki; Małgorzata Piekarska-Kasperska; Aleksandra Maciejczyk; Katarzyna Krupa; Julia Błoniecka; Kacper Jankowski; Anna Daniel (International Journal of Innovative Technologies in Social Science, 2025)
Schizophrenia is a complex psychiatric disorder with multifactorial pathophysiology, involving neuroinflammation, oxidative stress, and metabolic disturbances. In recent years, increasing attention has been directed toward the role of diet in modulating mental health, including the onset and progression of schizophrenia. This review explores the potential impact of specific nutrients, dietary patterns, and gut microbiota on schizophrenia-related mechanisms. Evidence suggests that the Mediterranean diet, rich in anti-inflammatory and antioxidant compounds, may exert neuroprotective effects, while the Western diet appears to aggravate inflammatory and metabolic dysregulation. The ketogenic diet has also demonstrated potential benefits through modulation of neurotransmission and mitochondrial function, though its restrictive nature may limit adherence. A central element in these interactions is the gut-brain axis, with the gut microbiota emerging as a key mediator linking dietary factors to central nervous system function. Despite promising findings, current research is limited by a predominance of observational studies. Further randomized controlled trials are needed to assess the therapeutic value of dietary interventions and microbiota-targeted strategies in schizophrenia management.